A Bidirectional Label Propagation Based Computational Model for Potential Microbe-Disease Association Prediction - Wang, Lei; Wang, Yuqi; Li, Hao; Feng, Xiang; Yuan, Dawei; Yang, Jialiang (Frontiers in Microbiology, 2019)
A growing number of clinical observations have indicated that microbes are involved in a variety of important human diseases. It is obvious that in-depth investigation of correlations between microbes and diseases will benefit the prevention, early diagnosis and prognosis of diseases greatly. Hence, in this paper, based on known microbe-disease associations, a prediction model called NBLPIHMDA was proposed to infer potential microbe-disease associations. Specifically, two kinds of networks including the disease similarity network and the microbe similarity network were first constructed based on the Gaussian interaction profile kernel similarity. The bidirectional label propagation was then applied on these two kinds of networks to predict potential microbe-disease associations. We applied NBLPIHMDA on Human Microbe-Disease Association database (HMDAD), and compared it with 3 other recent published methods including LRLSHMDA, BiRWMP and KATZHMDA based on the Leave-One-Out Cross Validation and 5-fold Cross Validation respectively. As a result, the AUCs achieved by NBLPIHMDA were 0.8777 and 0.8958±0.0027 respectively, outperforming the compared methods. In addition, in case studies of asthma, colorectal carcinoma and COPD, simulation results illustrated that there are 10, 10 and 8 out of the top 10 predicted microbes having been confirmed by published documentary evidences, which further demonstrated that NBLPIHMDA is promising in predicting novel associations between diseases and microbes as well.